Arctic-like Rabies Virus, Bangladesh - Jamil, Khondoker Mahbuba; Ahmed, Kamruddin; Hossain, Moazzem; Matsumoto, Takashi; Ali, Mohammad Azmat; Hossain, Sohrab; Hossain, Shakhawat; Islam, Aminul; Nasiruddin, Mohammad; Nishizono, Akira
Arctic/Arctic-like rabies virus group 2 spread into Bangladesh â‰ˆ32 years ago. Because rabies is endemic to and a major public health problem in this country, we characterized this virus group. Its glycoprotein has 3 potential N-glycosylation sites that affect viral pathogenesis. Diversity of rabies virus might have public health implications in Bangladesh.